X-Particles 4 for Cinema 4D Essential Training. - Needham, Andy (linkedin.com, 2018)
Get started with X-Particles 4, the powerful Cinema 4D plugin that allows artists to quickly and easily create finely rendered fluid simulations, dynamics, and collisions.